Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00431-013-1986-7
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible encephalopathy syndrome with exercise-induced acute kidney injury in renal hypouricemia type 1

Abstract: Renal hypouricemia type 1 is caused by mutations in the SLC22A12 gene, whereas type 2 is caused by defects in the SLC2A9 gene. Although both subtypes predispose to exercise-induced acute kidney injury (EIAKI), posterior reversible encephalopathy syndrome (PRES) occurring with this disorder is an uncommon phenomenon that has only been reported to date in a patient with renal hypouricemia type 2. We describe a 13-year-old boy with renal hypouricemia type 1 (serum uric acid, 0.9 mg/dL) with a homozygous W258X mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…PRH is associated with low sUA levels, nephrolithiasis, and exercise-induced acute failure (EIARF). Several authors have found an association between some neurological alterations of the posterior reversible encephalopathy syndrome and EIARF, supporting the hypothesis of a relation between changes of sUA levels and altered cognitive function [ 65 , 66 , 67 ].…”
Section: Mechanisms Underlying the Relation Between Ua And Cognitimentioning
confidence: 68%
“…PRH is associated with low sUA levels, nephrolithiasis, and exercise-induced acute failure (EIARF). Several authors have found an association between some neurological alterations of the posterior reversible encephalopathy syndrome and EIARF, supporting the hypothesis of a relation between changes of sUA levels and altered cognitive function [ 65 , 66 , 67 ].…”
Section: Mechanisms Underlying the Relation Between Ua And Cognitimentioning
confidence: 68%
“…While most patients are asymptomatic, episodes of the urolithiasis and exercise-induced acute kidney injury (EAKI) are sometimes observed [3, 4]. The increased risk of urolithiasis is due to hyperuricosuria and hypercalciuria [5]. Furthermore, the pathogenesis of EAKI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The histological finding of interlobular artery intimal thickening in a normotensive RHUC2 patient, attributed to repeated vasoconstriction, renders further support to this pathophysiological concept, which is also backed by CT findings showing patchy wedgeshaped enhancement in renal parenchyma [18,24] . Interestingly, evidence for a more systemic oxidant imbalance at presentation with AKI accumulates: 3 cases of posterior reversible encephalopathy syndrome have been recently reported in RHUC1 and RHUC2 patients, and one Japanese RHUC1 individual exhibited reversible T-wave inversion on ECG; together, these reports are suggestive of cerebral and coronary artery constriction, respectively [19,[24][25][26] . That being said, other disorders associated with hypouricemia, such as hereditary xanthinuria, are not usually associated with AKI.…”
Section: Discussionmentioning
confidence: 97%